Dedifferentiation in SDH-Deficient Gastrointestinal Stromal Tumor: A Report With Histologic, Immunophenotypic, and Molecular Characterization. (October 2019) - Malik, Faizan; Santiago, Teresa; Bahrami, Armita; Davis, Eric; McCarville, Beth; Newman, Scott; Azzato, Elizabeth M; Davidoff, Andrew M; Brennan, Rachel; Ellison, David W; Clay, Michael R
One-third of gastrointestinal stromal tumors (GISTs) that lack KIT or PDGFRA mutations show succinate dehydrogenase (SDH) mutations or promoter hypermethylation. Most SDH-deficient GISTs occur in the pediatric, adolescent, or young adult setting and have unique features including predilection for the stomach, multinodular plexiform architecture, epithelioid cytology, prominence of lymphovascular invasion, and predilection for nodal metastasis. Dedifferentiation in GIST is a rare histologic change which may occur de novo or secondary to imatinib therapy and is characterized by abrupt transition of well-differentiated (WD) GIST to a subclonal anaplastic process that shows loss of immunohistochemical marks (CD117, DOG1). We describe the case of a previously healthy 18-year-old man who presented with a large gastric wall mass that contained 2 distinct morphologic populations. The first was WD and characterized by sweeping fascicles of bland spindled cells. This population abruptly transitioned to dedifferentiated (DD) foci composed of large sheets of discohesive cells that displayed a spectrum of rhabdoid and epithelioid morphologies with marked pleomorphism and mitotic activity. Immunohistochemically, the tumor showed variable staining in the 2 components with diffuse DOG-1 and CD117 positivity in the WD component and complete absence in the DD foci. SDH-B staining was lost in both components. Whole exome and transcriptome analysis was performed on tissue from both components and both showed an SDHB mutation (c.286G>A) as well as unique mutational burden and copy number profiles. Herein, we describe the first case of a DD SDH-deficient GIST with morphologic, immunophenotypic, and molecular characterization.